Association between dietary inflammation and erectile dysfunction among US adults: A cross-sectional analysis of the National Health and Nutrition Examination Survey 2001–2004 - Ruan, Zhijie; Xie, Xiaoping; Yu, Haoyang; Liu, Ruimin; Jing, Wenjuan; Lu, Tao (Frontiers in Nutrition, 2022)
Background: Although chronic low-grade inflammation has been linked to the development of erectile dysfunction (ED), the association between pro-inflammatory diets and ED is unclear. The dietary inflammation index (DII) is a novel method to quantify the inflammatory potential of a diet. Objective: Our objective was to investigate the association between the DII and ED among US males. Design: This cross-sectional study included 3693 males 20–85 y of age from the NHANES 2001–2004. Multivariable-adjusted logistic regression models were used to assess the association between the DII and ED. All analyses accounted for the complex sampling design. Results: The mean ± SE of the DII was 0.8 ± 0.1 and 0.4 ± 0.1 among participants with and without ED, respectively. After adjusting for age, race/ethnicity, education, smoking status, physical activity, drinking status, hypertension, diabetes, cardiovascular disease, hypercholesterolemia, BMI, and eGFR, the DII score was associated with ED (odds ratio 1.12; 95% CI: 1.04–1.19). Moreover, this association was also stable in our subgroup analysis or sensitivity analyses. Conclusions: Dietary inflammatory potential, as estimated by the DII score, is positively associated with ED among US males.